Emotional processing is not enough: relations among resilience, emotional approach coping, and posttraumatic stress symptoms among combat veterans - Shorer, Shai; Weinberg, Michael; Cohen, Lihi; Marom, Doron; Cohen, Miri (Frontiers in Psychology, 2024)
Combat soldiers are exposed to various potentially traumatic events and face high risk of developing military-related psychopathology, such as depression, posttraumatic stress and grief (PTSS). However, a strong body of research shows that resilience is the default in the aftermath of trauma and indeed, many veterans do not develop high symptomatic levels. To explicate this inconsistency, the current study examined the associations among PTSS, resilience, and patterns of emotional-approach coping. A sample of 595 male combat veterans filled out questionnaires on trauma exposure, PTSS, depressive symptoms, resilience, and emotional-approach coping. Their data were analyzed using structural equation modeling path analysis. Participants reported high exposure to potentially traumatic events during service. Mean scores were high for resilience and relatively low for PTSS and depressive symptoms; 13% had a clinical level of posttraumatic stress disorder. Structural equation modeling revealed that emotional-approach coping strategies mediated the relationship between resilience and PTSS. However, emotional expression was associated with lower PTSS levels, whereas emotional processing was associated with higher PTSS levels. These results suggest that although emotional-approach coping was related to higher resilience, emotional expression (an intrapersonal coping strategy) might have a more positive effect than self-oriented emotional coping strategies. Providing veterans with supportive opportunities and a wider repertoire of emotional coping skills might enhance their well-being, reduce postservice emotional distress while not harming veterans’ resilience levels.